Analysis the Quality of Biofertilizers Made from Local Biomass with Variations of Microbial Bioactivators to Support Ngada Regency Organic Agriculture - Antonia P. Bao; Umbu N. Limbu; Monika M. Meo; Silverius Betu (Jurnal Biologi Tropis, 2026)
In line with Ngada Regency long-term plan to achieve eco-friendly farming/ go organic, the demand for high-quality organic inputs continues to increase. However, that areas still face limitations in the supply of organic fertilizers and the high prices of chemical fertilizers, which hinder the optimization of crop yields. The agricultural, rice milling, local wood processing industries and farm produce abundant biomass like green leaves, dry leaves, rice husks, sawdust, and manure which have not yet been optimally utilized. In fact, the combination of that biomass has a complex nutrient that is potential as a biofertilizer to restore soil fertility. However, lignin and cellulose wood materials such as sawdust and rice husks require a long natural decomposition time, so fermentation technology using microbial bioactivator agents is needed to accelerate the breakdown of these organic materials. The purpose is to analyze the characteristics of the fermentation process on a mixture of the biomass using different types of microbial bioactivators, namely decomposer microbes, local microorganisms from rice soaking, and soil microbes from bamboo roots. The research used fermentation method with a Completely Randomized Design research design and physical quality include temperature, pH, color, aroma, and biofertilizer texture. The results show that all bioactivators successfully decomposed the local biomass mixture within 35 days. The treatment using bamboo root soil microbes showed the best physical quality results with the fastest temperature stability, ideal neutral pH (7.2), dark black humus color, fresh soil aroma, and the finest and crumbliest fertilizer texture.